“SIWANPEKERJA” : THE INFORMATION SYSTEM OF ENTREPRENEURSHIP, THE TRADITIONAL REGIONAL FOOD SPECIALTIES (KERUPUK, RENDANG AND SANJAI) IN PAYAKUMBUH. - Mary, M. Kom, Thomson; Mary, Thomson (Jurnal EDik Informatika, 2017)
Abstract The paper is based on research results on Small and Medium Enterprises in Indonesia where its scope in Payakumbuh city of West Sumatra Province. A survey conducted in 2014 until early 2015 in some units of small and medium enterprises in the city Pakumbuh include traditional food business; crackers, Sanjai and rendang. The business is still run by the traditional and still do not have an integrated information system that is adequate and do not have a database that is useless for mapping potential areas of culinary tourism, business development to the continued efforts of government assistance. The system will be built to collect all data about them in the Enterprise Information System Crackers, Sanjai and Rendang (Siwanpekerja). Data were analyzed with a system of SDLC (System Development Life cicle) that encapsulates the actors involved in this project. The Actors are ; User system from a cottage industry entrepreneurs, Sellers, Buyers and Governments are summarized in an integrated information system that Payakumbuh has the most complete database in the development of culinary tourism in Indonesia. The results obtained in this study is in the form of an information system "Siwanpekerja" to accommodate the actors to belong in a database so Payakumbuh government and the Small and Medium businesses benefit greatl. Conclusion of "Siwankapus" has certain advantages, namely; facilitate the provision of assistance from the government, facilitate marketing, and entrepreneurial development for the futureKeywords : Information System, Traditional Food, Culinary Tourism,